Digital hygiene skills and cyberbullying reduction: a study among teenagers in Kazakhstan - Berdi, Dinara; Niyazova, Gulzhan; Bayterekova, Nurbanu; Koshanova, Gulnazira; Usembayeva, Indira (Institute of Advanced Engineering and Science, 2024)
Cyberbullying is a growing concern among teenagers, leading to adverse psychological and emotional consequences. To address this issue, this study aimed to identify the role of digital hygiene skills in reducing cyberbullying experiences among teenagers in Kazakhstan. A quantitative research approach was employed, and the data were collected using a questionnaire with items related to digital hygiene skills and cyberbullying experiences, which were measured on a 5-point Likert scale. A stratified random sample of 238 students from town and district middle schools in the Turkistan region participated in the study. The data were analyzed using partial least squares structural equation modeling with SmartPLS 4.0. The findings revealed that privacy protection, critical thinking, phishing and scam awareness, and digital footprint awareness were significant factors associated with reduced cyberbullying experiences. However, safe reporting, positive online behavior, and online etiquette did not significantly impact cyberbullying reduction. This study underscores the importance of promoting specific digital hygiene skills to create a safer and more supportive digital environment for teenagers. Policy recommendations are provided to enhance cyberbullying prevention efforts and foster a positive online culture.